Cryptography apocalypse : preparing for the day when quantum computing breaks today's crypto - Grimes, Roger A. (Hoboken, NJ : Wiley, 2020)
Providing a simple quantum mechanics primer, this book is an indispensable resource for every IT and InfoSec professional responsible for making appropriate decisions to meet the challenges of the coming quantum-computing revolution. --
Front Matter -- Quantum Computing Primer. Introduction to Quantum Mechanics -- Introduction to Quantum Computers -- How Can Quantum Computing Break Today's Cryptography? -- When Will the Quantum Crypto Break Happen? -- What Will a Post-Quantum World Look Like? -- Preparing for the Quantum Break. Quantum-Resistant Cryptography -- Quantum Cryptography -- Quantum Networking -- Preparing Now -- Appendix -- Index.
Includes index.
Online resource; title from PDF title page (John Wiley, viewed October 22, 2019).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Data encryption (Computer science); Cryptography; Quantum computing; Chiffrement (Informatique); Cryptographie; Informatique quantique; Cryptography; Data encryption (Computer science); Quantum computing